IMPROVING OF ENERGY AND OTHER INDICATORS OF RECEIVING AND ACCEPTANCE TESTING OF ELECTRIC LOCOMOTIVES TRACTION MOTORS - Loza, P. O. (Science and Transport Progress, 2009)
The methods of determination of equivalent load current in tests of electric locomotive traction engines without forced ventilation with use of the results of qualification test of engines of certain types are offered in the article.